Estimating posttraumatic stress disorder severity in the presence of differential item functioning across populations, comorbidities, and interview measures: Introduction to Project Harmony. Issue 3 (5th February 2022) - Morgan‐López, Antonio A.; Hien, Denise A.; Saraiya, Tanya C.; Saavedra, Lissette M.; Norman, Sonya B.; Killeen, Therese K.; Simpson, Tracy L.; Fitzpatrick, Skye; Mills, Katherine L.; Ruglass, Lesia M.; Back, Sudie E.; López‐Castro, Teresa; et al.
Abstract: Multiple factor analytic and item response theory studies have shown that items/symptoms vary in their relative clinical weights in structured interview measures for posttraumatic stress disorder (PTSD). Despite these findings, the use of total scores, which treat symptoms as though they are equally weighted, predominates in practice, with the consequence of undermining the precision of clinical decision‐making. We conducted an integrative data analysis (IDA) study to harmonize PTSD structured interview data (i.e., recoding of items to a common symptom metric) from 25 studies (total N = 2, 568). We aimed to identify (a) measurement noninvariance/differential item functioning (MNI/DIF) across multiple populations, psychiatric comorbidities, and interview measures simultaneously and (b) differences in inferences regarding underlying PTSD severity between scale scores estimated using moderated nonlinear factor analysis (MNLFA) and a total score analog model (TSA). Several predictors of MNI/DIF impacted effect size differences in underlying severity across scale scoring methods. Notably, we observed MNI/DIF substantial enough to bias inferences on underlying PTSD severity for two groups: African Americans and incarcerated women. The findings highlight two issues raised elsewhere in the PTSD psychometrics literature: (a) bias in characterizing underlying PTSD severity and individual‐level treatment outcomes when the psychometric model underlying total scores fails to fit the data and (b) higher latent severity scores, on average, when using DSM‐5 (net of MNI/DIF) criteria, by which multiple factors (e.g., Criterion A discordance across DSM editions, changes to the number/type of symptom clusters, changes to the symptoms themselves) may have impacted severity scoring for some patients.